Understanding Zillennials Consumer Green Behavior of Reducing Plastic Bag Use through the Theory of Planned and Interpersonal Behavior - Solekah, Nihayatu Aslamatis; Handriana, Tanti; Usman, Indrianawati (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2024)
Adopting cloth bags over single-use plastic bags is a significant consumer behavior. Employing the theory of of planned and interpersonal behavior, this study aimed to understand the relationship between customers' intentions to use cloth bags and their awareness of the environmental impact of plastic bags. Through purposive sampling, 277 individuals born after 1980 and making at least one to three in-person retail and Internet purchases each month were selected as participants. The data were processed using descriptive and quantitative analysis tools using SEM (Structural Equation Model) analysis. The findings reveal that creating the next generation of habit bags can significantly enhance social awareness of plastic bag usage and the environment. However, no evidence suggests that the EAPB increases the intention to use cloth bags. The more the SP and SBPB intervene, the more the IUCB contributes to changing consumer behavior to use fewer plastic bags. Therefore, Habit Bag Use can positively influence pro-environmental behavior, as this study combined the theory of Interpersonal Behavior and the theory of Planned Behavior. These results contribute to the theoretical framework for understanding how the millennial generation's interpersonal conduct, reflected in their bag-using behaviors, influences their behavior in minimizing plastic bag usage. These findings imply that the adoption of single-use or non-plastic bag habits can motivate people to reduce their usage of plastic bags, a behavior that is further encouraged by laws prohibiting the use of plastic bags.